COMPARATIVE PROSPECTIVE STUDY SINGLE BLIND RANDOMIZED CONTROLLED TRIAL TO ASSESS THE EFFICACY AND SAFETY OF SECNIDAZOLE WITH N-ACETYL CYSTEINE IN PATIENTS WITH BACTERIAL VAGINOSIS AMONG REPRODUCTIVE WOMEN IN A TERTIARY CARE HOSPITAL - Dr. Deepthi Krishna; Dr. D. Dharam Prasath; Dr. P. Jacob Verghese; Dr. E. Seshathri (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Secnidazole has been proven to have antimicrobial activity against many bacterial species that are involved in BV. Similar to other 5-nitroimidazoles, it has limited activity against lactobacilli, which are beneficial microbes crucial for re-establishing vaginal health post-treatment. However, the tolerability profile of secnidazole closely resembles that of other 5-nitroimidazoles. The most frequently reported adverse events in clinical trials were nausea, vomiting, glossitis, anorexia, epigastric pain, and a metallic taste. Whereas NAC (N-acetyl cysteine) stimulates glutathione synthesis, promotes detoxification, and acts directly as a scavenger of free radicals, making it a powerful antioxidant. some study also reported its choriodecidual protecting effect and its anti-inflammatory properties in the pregnant women with bacterial vaginosis. Objective: To compare the effectiveness and safety of Secnidazole with N-acetyl cysteine for treating Bacterial Vaginosis in reproductive women at a Tertiary care hospital. Methods: This was a single blinded randomized experimental stud. Patients received either Secnidazole (2g/day) alone (monotherapy) or the combination of Secnidazole (2g/day) with N-acetyl cysteine (600mg/day. The treatment period was four weeks, and both medications were administered orally once daily. Patients were requested to come for follow-up at the 2nd and 3rd month from the date of the end of the initial treatment for the assessment of recurrence. Safety evaluations were conducted to assess the incidence, intensity, and type of adverse events, as well as changes in the patients’ physical examination findings, vital signs, and clinical laboratory findings in both groups. Results: An Independent t-test was conducted to compare both groups. There was a statistically significant difference in the symptomatic cure (5 out of 45 patients in the secnidazole group, and none out of 45 patients in the secnidazole with NAC group; p-value < 0.01) and positive whiff test (4 out of 45 patients in the secnidazole group, and none out of 45 patients in the secnidazole with NAC group; p-value < 0.01). Additionally, there were statistically significant differences in the mean ± SD of baseline Nugent score between the two groups (4.20 ± 1.37 in secnidazole group vs. 2.67 ± 0.87 in secnidazole with NAC group; p-value < 0.01*). Conclusion: Our study recommends that the results of combining secnidazole with N-acetyl cysteine have been very promising for the broader clinical use of NAC as an adjuvant therapy for bacterial vaginosis